Identifing Some Risk Factors of Female Secondary Infertility - B, Munkhnaran; G, Tsendmaa; G, Davaa; B, Bolorchimeg (Caucasus Journal of Health Sciences and Public Health, 2020)
Countries in the world had categorized with high reproductive ability (more than 3.2 children) and low reproductive ability (less than 2.0 children) at world health report-2013 from WHO. In 2010, 66 countries were high reproductive ability (United Nations and Social Affairs 2013). Mongolian women had average 4.3 children in 1990, and in 2014 it decreased to 3.1 children. So Mongolia had discarded from high reproductive ability category. Women’s birth rate decreases, while infertility spreads are increasing. The infertility epidemic in the world is 8.0-29.0% (Pandey et al., 2014). In 2003, Mongolian infertility rate was 8.7% (NHCMC, 2003) and increased to 11.6% in 2013 (I. Purevogtokhok 2013). According to Mongolian researchers, 45.8% of the causes of infertility female infertility, 25.6% are male factor and 18.8% are due to men and women, and cause unspecified infertility 9.8% (NCHD 2003). The proportion of female infertility in the infertile structure accounts was the highest proportion. Although there are studies on the risk factors for female and male infertility in Mongolia, there are no studies on the risk factors of secondary infertility in women.